EMERGING TRENDS OF DIGITAL PUBLIC SPACES: A BIBLIOMETRIC ANALYSIS BASED ON VOSVIEWER - Carissa Dinar Aguspriyanti (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: This paper investigated the emerging trends of research related to digital public spaces through a bibliometric analysis based on the VOSviewer software. Digital public spaces have become a hot topic of conversation lately due to possible influencing factors like the development of advanced Industry 4.0 technologies, the introduction of Society 5.0, the growth of smart city concept, the manifestation of the digital universe as known as metaverse, and the COVID-19 pandemic. A total of 610 publications obtained from the Scopus database were analysed in three different ways including research development trends analysis, publications productivity analysis, and knowledge topic area analysis. The results pointed out that from 2012 to 2021, digital public spaces have attracted the significant attention of researchers in various scientific fields, mostly in western countries. From 7 clusters of knowledge topic areas detected, public space, social media, human-computer interaction, urban planning, and digital technologies have established the research hotspot to date. In addition, as the research focus is enriching, the potential novelty for further digital public spaces research may likely be related to more comprehensive and humane aspects. It is also possible that linking unrelated topics between different clusters is also highly considered to obtain the novelty of future research.Abstrak: Makalah ini menyelidiki tren penelitian yang muncul terkait dengan ruang publik digital melalui analisis bibliometrik berdasarkan perangkat lunak VOSviewer. Ruang publik digital menjadi perbincangan hangat akhir-akhir ini karena faktor-faktor yang berpotensi mempengaruhi seperti perkembangan teknologi maju Industri 4.0, pengenalan Society 5.0, pertumbuhan konsep kota pintar, manifestasi dunia digital yang dikenal sebagai metaverse, dan pandemi COVID-19. Sebanyak 610 publikasi yang diperoleh dari database Scopus dianalisis dengan tiga cara berbeda meliputi analisis tren pengembangan penelitian, analisis produktivitas publikasi, dan analisis area topik pengetahuan. Hasil penelitian menunjukkan bahwa dari tahun 2012 hingga 2021, ruang publik digital telah menarik perhatian yang signifikan dari para peneliti di berbagai bidang ilmiah, terutama di negara-negara barat. Dari 7 klaster bidang topik pengetahuan yang terdeteksi, ruang publik, media sosial, interaksi manusia-komputer, perencanaan kota, dan teknologi digital telah menjadi pusat topik penelitian hingga saat ini. Selain itu, seiring dengan bertambahnya fokus penelitian, potensi kebaruan untuk penelitian ruang publik digital lebih lanjut dapat berkaitan dengan aspek yang lebih komprehensif dan manusiawi. Menghubungkan topik-topik yang tidak terkait antar klaster yang berbeda juga dapat dipertimbangkan untuk mendapatkan kebaruan penelitian masa depan.